Impact simulation of ECOWAS rice self-sufficiency policy - Fofana, Ismaël; Goundan, Anatole; Magne Domgho, Léa Vicky (International Food Policy Research Institute, 2014)
Rice is a strategic commodity for food security in West Africa. Its consumption has grown rapidly over time as a result of population growth, urbanization, and increasing purchasing power. Dependency on imported rice exposes the region to external shocks stemming from the global market. Given its economic and social importance, most countries in West Africa have developed a national strategy for rice development alongside their agricultural sector-wide policy. In addition, the Economic Community of West African States is actively supportive of national strategies under a regional offensive to boost rice production and meet the challenge of rice self-sufficiency in the region by 2025. Our analysis uses economic models to forecast rice consumption, and then simulates the economywide impacts of achieving rice self-sufficiency in West Africa. Results show that per capita consumption of rice is expected to increase from 44 to 53 kilograms on average between 2011 and 2025.